Ovarian function in the gilt and lactating sow - Grant, Shona Agnes (1989)
Maturational changes during the follicular phase of the porcine oestrous cycle were investigated in spontaneously cycling gilts. The results revealed considerable variation in the morphological and biochemical development of dominant follicles in the early follicular phase. This asynchrony was emphasised by the marked differences in follicular fluid steroid concentrations and LH binding to granulose cells and theca tissue between follicles of identical size within the same ovary. The nature of this variation may have great significance on our present understanding of asynchronies in embryo development.